The Euthalian Tradition of the New Testament: A Catalogue of Greek Manuscripts - Allen, Garrick V.; Fowler, Kimberley A.; Scieri, Emanuele; Venetskov, Maxim (Brill, 2025)
The Euthalian tradition is a complex and pervasive set of late ancient prefaces, lists, divisions, and other paratexts transmitted alongside Acts, the Catholic Epistles, and Pauline Epistles, preserved (at least in part) in over 600 Greek manuscripts. This book catalogues the extent of the Euthalian tradition, introducing these features, pointing to their significance for research on the New Testament, and mapping their distribution in manuscripts produced from the sixth century onward. This catalogue is a tool for further research on the New Testament’s Greek manuscripts, reception history, and intellectual context.